Why are predator cues in the field not more evocative? A ‘real world’ assay elicits subtle, but meaningful, responses by wild rodents to predator scents - Parsons, Michael H.; Stryjek, Rafal; Bebas, Piotr; Fendt, Markus; Blumstein, Daniel T.; Kiyokawa, Yasushi; Chrzanowski, Marcin M.; Munshi-South, Jason (Frontiers in Ecology and Evolution, 2023)
Mismatches between highly-standardized laboratory predatory assays and more realistic environmental conditions may lead to different outcomes. Understanding rodents’ natural responses to predator scents is important. Thus, field studies on the same and related species are essential to corroborate laboratory findings to better understand the contexts and motivational drives that affect laboratory responses to predator scents. However, there are too few field assays to enable researchers to study factors that influence these responses in genetically variable populations of wild rodents. Therefore, we placed laboratory-style chambers and remote-sensing devices near multiple colonies of two species of wild mice (Apodemus agrarius and A. flavicollis) to test dual-motivational drives (appetitive and aversive) in a ‘familiar’ yet natural environment. A highly-palatable food reward was offered daily alongside scents from coyotes, lions, rabbits, and both wet and dry controls. In all but two instances (n=264), animals entered chambers and remained inside for several minutes. Animals initiated flight twice, but they never froze. Rather, they visited chambers more often and stayed inside longer when predatory scents were deployed. The total time spent inside was highest for lion urine (380% longer than the dry control), followed by coyote scent (75% longer), dry control and lastly, herbivore scents (no difference). Once inside the chamber, animals spent more time physically interacting with predatory scents than the herbivore scent or controls. Our findings support the common assumption that rodents fail to respond as overtly to predatory scents in the field compared to what has been observed in the laboratory, possibly due to their varying motivational levels to obtain food. More time spent interacting with scents in the field was likely a function of ‘predator inspection’ (risk assessment) once subjects were in a presumed safe enclosure. We conclude this sort of chamber assay can be useful in understanding the contexts and motivational drives inherent to field studies, and may help interpret laboratory results. Our results also suggest more attention should be given to subtle behaviors such as scent inspection in order to better understand how, and when, environmental stimuli evoke fear in rodents.